PERAWATAN HOSPIS DALAM KONTEKS KEPERAWATAN: ANALISIS KONSEP - Khalid Khan; Yeni Rustina; Murad Ali (Jurnal Keperawatan Widya Gantari Indonesia, 2026)
Hospice care is widely used in nursing practice; however, its meaning remains unclear and is often used interchangeably with palliative and end-of-life care, resulting in conceptual ambiguity. This study aimed to clarify the concept of hospice care in the context of nursing. Walker and Avant’s eight-step concept analysis approach was applied. A literature review was conducted using the keywords Hospice care AND Nursing across PubMed, CINAHL, Scopus, and ProQuest databases, including English-language articles published between 2000 and 2025. The defining attributes of hospice care were identified as (1) comfort-focused, not curative care, (2) holistic care, and (3) support during the dying process. Antecedents included a diagnosis of terminal illness, prognosis of limited life expectancy, and the patient’s informed decision to forego curative treatment. Consequences were enhanced comfort and symptom control, improved quality of life for patients and families, and a peaceful and dignified death experience. This concept analysis provided conceptual clarity of hospice care in nursing and can guide nursing practice, education, and future research in end-of-life care.